TRADISI GREBEG SUDIRO DI SUDIROPRAJAN (AKULTURASI KEBUDAYAAN TIONGHOA DENGAN KEBUDAYAAN JAWA) - Adriana, Tissania Clarasati (Candi, 2013)
The purpose of this study were (1) To determine the background of the ceremony in Sudiroprajan Sudiro Grebeg tradition, (2) process Grebeg Sudiro the ceremony tradition, (3) Acculturation of Chinese culture with Java in Grebeg Sudiro. The research was conducted using qualitative methods in Sudiroprajan ethnographic approach. The strategy is a case study of a single glued. Data sources used include informants, places and events and documents. Sampling is used purposive sampling and snowball sampling. Data collection techniques used were interviews, observation and document analysis. The validity of data using triangulation of data and the triangulation method. Technique analiisis data using interactive analysis model is interaction between the three components of data analysis with data collection cycle. Based on these results it can be concluded: (1) Grebeg Sudiro formed due to the awareness and intention of the citizens Sudiroprajan to show the harmony and the harmony that exists between two different ethnic (2) The ceremonial procession tradition Sudiro Grebeg include various series of events that must be passed among is pre dinner charity event Bok Teko earth January 12th 2012 and the top event Grebeg Sudiro which took place on January 15, 2012 event in which both have requirements that must be met, and complete the necessary equipment ceremony. (3) Acculturation of Chinese culture with the tradition of Javanese culture Grebeg Sudiro mountains visible in the arrangement of the two pie basket Estri Mountains and the Mountains Jaler normally found in traditional Javanese, and Lion Dance Liong look a ritual ceremony before the show, because of prior experience acculturation with Javanese cultural performances and Lion Dance Liong not familiar ritual and Javanese traditional music Keroncong collaborated with Mandarin song called Keroncong Mandarin. Keyword : Tradition, acculturation,ceremony, culture.